Evaluation of environmental education as a strategy for sustainable development in Sri Lanka - Ruzaik, Fareena (INSTITUTE OF HUMAN RESOURCE ADVANCEMENT, University of Colombo., 2020)
Abstract The human and environmental relationship has a boundless integration, due to its interdependency. Environmental resources are utilized by human beings to meet their daily needs in the context of consumption and development. This process has a negative impact on the environment and human health. Predominantly environmental-related issues are induced by human activities. However, these issues could be minimized by way of maintaining a balance between development and utilization of resources, fulfilling present needs without compromising the needs of future generations as correctly elaborated in the Brundtland Commission Report (1987). Accordingly, the objective of this paper is to evaluate the contribution of environmental education and awareness in terms of sustainable development to adapt the general public to be environmentally conscious. The extracted data and information only from secondary sources have been sorted and analyzed, following the qualitative approach; while constructing environmental education as a tool for productive sustainable development approach. This study found that the Central Environmental Authority (CEA), is a major institution that extends the many environmental education and awareness program to the various target group, such as school students, teachers, Grama Niladharies, Samurdhi Niladharies, and Development Officers. In addition, other government and nongovernment organizations provide similar services to the general public to safeguard the environment. This study recommends, having a collective mechanism to promote environmental education and awareness to the public with the participation of relevant stakeholders.
Evaluation of environmental education as a strategy for sustainable development in Sri Lanka
Journal of IHRA, Volume.7 Issue.2 December 2020
Keywords: Interdependency, impacts, environment, education, sustainable development.